2017
DOI: 10.18203/issn.2455-4510.intjresorthop20172503
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcome of extra articular lower end radius fracture with percutaneous pinning and volar locking plate

Abstract: INTRODUCTIONFractures of the distal radius are common fractures seen in orthopedics outpatient and trauma care. Data suggests that around 6% of women by age of 80 years will sustain such fracture and 9% women by age of 90.1 As the population continues to age, these figures are likely to increase still further. Its growing incidence may be attributed to a parallel rise of osteoporosis and high energy accidents.2,3 The epidemiology has changed from the times of Colle's fracture to present date due to increased l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Multiple linear regression (MLR) models were adopted for multivariate analysis of the DASH scores to identify the significant predictor variables. From the literature, we found that age, sex, ethnicity, type of fractures, clinicians involved, type of anaesthetic techniques and POP used affected the outcome of DRF. Therefore, we took those variables into consideration during developing MLR models.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Multiple linear regression (MLR) models were adopted for multivariate analysis of the DASH scores to identify the significant predictor variables. From the literature, we found that age, sex, ethnicity, type of fractures, clinicians involved, type of anaesthetic techniques and POP used affected the outcome of DRF. Therefore, we took those variables into consideration during developing MLR models.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, ‘group’ was our variable of interest. In addition, we have considered age, sex, ethnicity, type of fractures, clinicians involved, type of anaesthetic techniques and POP used as confounders and potential predictor variables. To make it clinically meaningful, continuous variables such as the age of the patients were centred .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Arthroscopic-assisted reduction during external fixation enhances the ability to achieve satisfactory reduction due to the direct visualization of the joint surface and concomitant assessment of the wrist ligaments. In recent times, with the advent of lower-profile polyaxial locking screw implants, it has become easier to address fractures with extensive fragmentation, variations in normal anatomy, and dorsal metaphyseal instability with a single surface implant leading to the increased popularity of the open reduction and internal fixation of these fractures among surgeons [11][12].…”
Section: Figure 3: Graph Showing Modified Green and O'brien Scores At Dmentioning
confidence: 99%